Ответы и объяснения

2013-12-25T14:25:47+00:00
Выражение: -(5-9)+(-3)*(X+5)Ответ: -11-3*XРешаем по действиям:
1. 5-9=-4
  -9
   _5_
  -4
2. -(-4)=4
3. (-3)*(X+5)=-3*(X+5)
4. 3*(X+5)=3*X+15
  3*(X+5)=3*X+3*5
  4.1. 3*5=15
      X3
       _5_
      15
5. -(3*X+15)=-3*X-15
6. 4+(-3*X-15)=4-3*X-15
7. 4-15=-11
  -15
   _ _4_
  -11
Решаем по шагам:
1. -(-4)+(-3)*(X+5)
  1.1. 5-9=-4
      -9
       _5_
      -4
2. 4+(-3)*(X+5)
  2.1. -(-4)=4
3. 4+(-3*(X+5))
  3.1. (-3)*(X+5)=-3*(X+5)
4. 4+(-(3*X+15))
  4.1. 3*(X+5)=3*X+15
      3*(X+5)=3*X+3*5
    4.1.1. 3*5=15
          X3
           _5_
          15
5. 4+(-3*X-15)
  5.1. -(3*X+15)=-3*X-15
6. 4-3*X-15
  6.1. 4+(-3*X-15)=4-3*X-15
7. -11-3*X
  7.1. 4-15=-11
      -15
       _ _4_                               вроде так
      -11